PENINGKATAN HASIL BELAJAR PERUBAHAN WUJUD ZAT MENGGUNAKAN MODEL DISCOVERY LEARNING DI KELAS III SDN 21 BANDAR BUAT KOTA PADANG - Aulia Fadira, Yaumi; Masniladevi; Ahmad, Syafri; Suciana, Fadila (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study addresses the low science achievement of third-grade students at SDN 21 Bandar Buat, which is associated with a largely teacher-centered instructional approach, limited student engagement, and the inadequate use of observation and experimental activities in the learning process. These conditions result in students being passive, less confident in asking questions, and struggling to understand concepts independently, which in turn leads to unsatisfactory learning outcomes and insufficient development of critical thinking skills. Moreover, classroom practices have not been fully aligned with the expectations of the Independent Curriculum. Therefore, this research aims to investigate the improvement of student learning outcomes on the topic of changes in the states of matter through the implementation of the Discovery Learning model in a third-grade classroom. This study employs a Classroom Action Research design, integrating both qualitative and quantitative approaches, and is conducted in two cycles. The first cycle consists of two meetings, while the second cycle includes one meeting, following stages of planning, action, observation, and reflection. The research instruments include observation sheets for lesson planning (RPPM), teacher and student activities, as well as assessment rubrics covering attitudes, knowledge, and skills. The participants consist of one teacher and 24 students. The results reveal consistent improvements in all observed aspects, including lesson planning, teacher and student activities, and overall learning outcomes, confirming the effectiveness of the Discovery Learning model.